TNF Receptor 1 Promotes Early-Life Immunity and Protects against Colitis in Mice - Cambrian Y. Liu; Sharon S. Tam; Ying Huang; Philip E. Dubé; Rabea Alhosh; Nandini Girish; Shivesh Punit; Shirin Nataneli; Fan Li; Jeffrey M. Bender; M. Kay Washington; D. Brent Polk (Cell Reports, 2020)
Summary: Neutralization of tumor necrosis factor (TNF) represents a widely used therapeutic strategy for autoimmune diseases including inflammatory bowel disease (IBD). However, the fact that many patients with IBD are non-responsive to anti-TNF therapies suggests the need for a better understanding of TNF signaling in IBD. Here, we show that co-deletion of TNF receptor 1 (TNFR1, Tnfrsf1a) in the Il10−/− spontaneous colitis model exacerbates disease, resulting in very-early-onset inflammation after weaning. The disease can be interrupted by treatment with antibiotics. The single deletion of TNFR1 induces subclinical colonic epithelial dysfunction and mucosal immune abnormalities, including accumulation of neutrophils and depletion of B cells. During the pre-disease period (before weaning), both Tnfr1−/− and Il10−/− Tnfr1−/− animals exhibit impaired expression of pro-inflammatory cytokines compared with wild-type and Il10−/− controls, respectively. Collectively, these results demonstrate the net anti-inflammatory functions of TNF/TNFR1 signaling through the regulation of colonic immune homeostasis in early life.